2018
DOI: 10.2147/cmar.s171589
|View full text |Cite
|
Sign up to set email alerts
|

Surgical intervention may be a therapeutic option for NSCLC patients with AJCC stage IV: a large population-based study

Abstract: BackgroundFew studies have focused on the role of surgery in the treatment of stage IV non-small cell lung cancer (NSCLC). In our study, we mainly focused on the surgical therapeutic option for NSCLC patients with American Joint Committee on Cancer stage IV.Patients and methodsUsing the Surveillance Epidemiology and End Results database, we screened out an appropriate patient population with stage IV NSCLC treated between 2004 and 2013. Kaplan–Meier curve analysis was used to compare the survival between patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Stage was important in another study in which those with stages I or II had a median OS of 5.6 compared to 3.5 years in those receiving stereotactic body radiation therapy (SBRT) ( 22 ). In adult patients, but not necessarily elderly, with stage IV NSCLC, surgery for primary and metastatic sites were predictive of OS, and survival benefits were not found in metastasis surgery for those with squamous or large cell carcinoma or N1 staging; and the maximum benefit was shown in NSCLC patients receiving primary site surgeries with stage N0 ( 23 ). Another study of aggressive surgical strategy for stage IV NSCLC showed a 5-year OS of 23.3% and a disease-free survival of 15.8%; those authors suggested that surgical treatment of stage IV disease can extend life only if the patients can tolerate surgery, which may again exclude elderly patients ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stage was important in another study in which those with stages I or II had a median OS of 5.6 compared to 3.5 years in those receiving stereotactic body radiation therapy (SBRT) ( 22 ). In adult patients, but not necessarily elderly, with stage IV NSCLC, surgery for primary and metastatic sites were predictive of OS, and survival benefits were not found in metastasis surgery for those with squamous or large cell carcinoma or N1 staging; and the maximum benefit was shown in NSCLC patients receiving primary site surgeries with stage N0 ( 23 ). Another study of aggressive surgical strategy for stage IV NSCLC showed a 5-year OS of 23.3% and a disease-free survival of 15.8%; those authors suggested that surgical treatment of stage IV disease can extend life only if the patients can tolerate surgery, which may again exclude elderly patients ( 24 ).…”
Section: Discussionmentioning
confidence: 99%